2013
DOI: 10.1097/prs.0b013e31827c6fab
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol versus Corticosteroids in the Treatment of Infantile Hemangioma

Abstract: Propranolol is a relatively recent therapy of hemangiomas with fewer side effects, a different mechanism of action, and greater efficacy than current first-line corticosteroid therapy. Many of these studies do not have the same patient population or duration/regimen of treatment for hemangiomas; however, based on available data in the literature, it appears that propranolol could be an emerging and effective treatment for infantile hemangiomas. Further randomized controlled trials are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 54 publications
(24 reference statements)
5
87
0
1
Order By: Relevance
“…The reported success rate from a systematic review and meta-analysis for all published series demonstrated an overall response rate of 97 % among patients treated with propranolol for infantile hemangioma versus a pooled response of 69 % for corticosteroids studies [8]; 0.9 % had propranolol-resistant infantile hemangiomas. Resistance was observed at all ages during early childhood and at any proliferation stage [3].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The reported success rate from a systematic review and meta-analysis for all published series demonstrated an overall response rate of 97 % among patients treated with propranolol for infantile hemangioma versus a pooled response of 69 % for corticosteroids studies [8]; 0.9 % had propranolol-resistant infantile hemangiomas. Resistance was observed at all ages during early childhood and at any proliferation stage [3].…”
Section: Discussionmentioning
confidence: 89%
“…A systematic review and meta-analysis of propranolol versus corticosteroids in the treatment of IH reported the lack of well-designed randomized clinical trials [8]. Systemic corticosteroids were considered the mainstay of therapy for hemangiomas.…”
Section: Introductionmentioning
confidence: 98%
“…Several other studies have reported similar observations with systemic propranolol. [15][16][17][18][19][20] Different hypotheses for the efficacy of this treatment have been proposed, including vasoconstriction, decreased levels of VEGF and FGF, and apoptosis of endothelial cells. Recently, a multicenter randomized controlled trial on 456 patients showed successful results in 88% of hemangiomas treated with propanolol compared with 5% with the placebo.…”
Section: Treatmentmentioning
confidence: 99%
“…[51][52][53] Malik and colleagues 51 designed a RCT comparing the efficacy of orally administered propranolol versus systemic steroids versus using both medications concurrently. The investigators showed that propranolol brought about earlier improved changes and that there was no significant increased benefit of adding prednisolone to propranolol, but this addition did lead to poorer patient compliance secondary to a higher number of complications associated with steroid use.…”
Section: Steroids-systemic/intralesionalmentioning
confidence: 99%